Simulação do equilíbrio: o método de Monte Carlo Equilibrium simulation: Monte Carlo method - Alejandro López-Castillo; José Cândido de Souza Filho (Química Nova, 2007)
We make several simulations using the Monte Carlo method in order to obtain the chemical equilibrium for several first-order reactions and one second-order reaction. We study several direct, reverse and consecutive reactions. These simulations show the fluctuations and relaxation time and help to understand the solution of the corresponding differential equations of chemical kinetics. This work was done in an undergraduate physical chemistry course at UNIFIEO.